Reassuring The Prevalence of Cerebral Palsy in Asian Children and Adolescents - Andromeda, Andromeda; Hartini, Nurul; Suryanto, Suryanto (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Cerebral palsy is becoming more common as a cause of developmental disorders in children. Several studies in low-income Asian countries found a higher prevalence of CP than in Europe. However, another study discovered the inverse result. The disparity in the results of these studies emphasizes the importance of the current study in updating the prevalence of CP in Asia. A systematic review and meta-analysis approach has been used in this study by searching for articles on three databases: PubMed, Scopus, and ScienceDirect. Eight articles were chosen through several screening stages and subjected to quality assessment. According to the study's findings, the prevalence of CP in Asia is 2.19 per 1000 children and adolescents (95% CI). Children and adolescents from low-income families have the highest incidence rate, with spastic-CP type being the most common classification.